Capital flows and endogenous growth - Evgenij Komarov (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
So-called "uphill capital flows", i.e. flows of physical capital from relatively poor to rich countries, are a new phenomenon with yet unclear impact. We develop a unified framework incorporating economic institutions, human capital and physical capital to study the interaction of international capital flows and growth. Analytically, we study conditions under which a positive change of a country's economic institutions can attract inflows of physical capital from abroad, leading to long-term growth via the accumulation of human capital. Our mechanism shows how a small initial difference in the level of institutions can lead to substantial divergence in income over time. We derive conditions under which a country receives inflows of capital over time and increases its investment in human capital. Finally, we provide simulations to illustrate our results.
Keywords: E02; F21; F43; O41; O43; 330; Growth; International Capital Flows; Inequality; Institutions; Human Capital